Popnacjonalizm, czyli elementy dyskursu (re)konstrukcji amerykańskiego poczucia tożsamości narodowej w wybranych filmach hollywoodzkich - Stawska , Marta (Studia Edukacyjne, 2023)
This article is dedicated to the idea of pop-nationalism and the connection between popular culture and how its productions (re)construct the American sense of national identity. The study is divided into subsections that delve into topics such as national identity in the current, fragmented social reality, the role of films in propagating American values during times of major socio-political crises, and the concept of banal nationalism according to Michael Billig. To analyze the elements of discourse, three films were chosen – Rocky IV (dir. Sylvester Stallone, 1985), Top Gun (dir. Tony Scott, 1986), and American Sniper (dir. Clint Eastwood, 2014). The research findings indicate that Hollywood films have a significant impact on building and reinforcing a sense of national pride and belonging in American society. Pop-nationalism is often used for entertainment purposes but also as a propaganda tool, especially during periods of international conflicts and political tensions.